THE CHANGES OF WOMEN’S IMAGE REPRESENTED BY SNOW WHITE CHARACTER IN MIRROR MIRROR MOVIE - PUTRI, KATRIZA ANDIKA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Nowadays, movie becomes one of favorite entertainmentsamong people.Not only for entertainment, movie can be the media to explore idea, opinion, and knowledge. There are a lot of genres in movie, for example drama, thriller,action, etc. Some of the exist movie, there is a fairytale or fiction story. Fairy talestories usually tells about prince and princess. Nevertheless, modernfairytale portrayed female domination in the story. The writer conducts a studyabout the changes of gender role as reflected in the movie Mirror Mirror. There is a problem to be solved, which is how Snow White as the main character in the movie changes the women image and gender role. As a comparative, the writer uses Snow White and the Seven Dwarfs movie. This study uses qualitative approach in relation to analyze the object material.To figure out the research question, the writer uses Gender Studies whichemploys three concepts, they are Traditional Gender Role, Patriarchal, and Gender Equalit This study uncovers Snow White experience in the changing of gender role and the image of woman. The result showsthat there is a changing of women image represent by Snow White in Mirror Mirror movie. Women in Mirror Mirror are no longer images as weak character. They now images as strong and brave character. It is recommended to do a further research in order to acquire new knowledge from this movie. The suggestion for the next researchersis that they can use Marxist theory from the capitalist point of view in analyzing this movie. It is to analyze how the power of  authority can involve the gender function in society. Keywords : gender role, women image